Early Neolithic Ritual Funerary Behaviours in the Westernmost Regions of the Mediterranean - García Rivero, Daniel (2021)
An intact archaeological context named Locus 1 has recently been discovered at Dehesilla Cave (southern Spain). The ritual funerary deposition consists of a complete pottery jar with part of a human calvarium over the mouth, and was occulted by large stone blocks. This paper offers a presentation of the new data provided mainly by the stratigraphic, osteological, pottery, lithic and radiocarbon analyses. A systematic review of the relevant evidence in the Iberian Peninsula during the Early Neolithic (c. 5600-4800 cal BC) provides a context for this finding and supports its interpretation with reference to several possible anthropological scenarios.